ANALISIS KUALITAS PELAYANAN PUBLIK GAJI PENSIUNAN TERHADAP KEPUASAN PELANGGAN PADA KANTOR POS UJUNG BERUNG KOTA BANDUNG - Nursyifa Lefiandi; Veronica Rizky (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to determine the quality of public services for pensioners' salaries onthe quality of services at the Ujung Berung Post Office, Bandung City. The researchmethod used is a quantitative method. For data collection techniques throughliterature study, observation, and questionnaires. And for the data analysis technique,the writer uses validity, reliability, correlation coefficient, determination coefficient,hypothesis testing using Microsoft Excel 2010 and SPSS 20 for windows. Based on theresults of the research that has been carried out, it can be concluded that there is arelationship between the influence of the variable X (Service Quality) on the Yvariable (Customer Satisfaction), it is known from the t test results that the t countvalue is higher than t table (5.081 > 1.697). The correlation coefficient value of 0.788means that the relationship between the influence of the variable X (Quality ofService) on the variable Y (Customer Satisfaction) is strong. The value of thecoefficient of determination of 0.620 means that the variable Y (CustomerSatisfaction) is influenced by the variable X (Service Quality) by 62.0% and the rest isinfluenced by other variables that the authors did not examine.